2020
DOI: 10.1029/2020jg006080
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment of Penguin Subcolonies in the Late Nineteenth Century on Inexpressible Island, Antarctica

Abstract: The impact of climate and weather on penguin ecology has attracted much research attention. To reconstruct the history of the penguin population, penguin carcasses on the surface and three ornithogenic sediment profiles were collected in a ditch area beneath abandoned penguin subcolonies on a high terrace to the northwest of the modern colony in Seaview Bay, on Inexpressible Island, East Antarctica. A rapid increase in penguin-derived element contents in the sediment profiles at~1700 Common Era (CE) indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…By comparing this grouping to previously published chemical analyses of penguin droppings, the authors confirmed that the group of bio-elements is representative of the species of interest, and so could be used to understand changes in penguin numbers back in time. R-cluster analysis, which has been used worldwide, is often considered the most effective tool to identify ornithogenic elements if a nearby reference site (i.e., a nearby lake without avian inputs) is not available to distinguish the natural, background element concentrations (Zale, 1994;Sun et al, 2000Sun et al, , 2004Liu et al, 2005Liu et al, , 2006cHuang et al, 2009aHuang et al, , 2011Xu et al, 2011Xu et al, , 2016Xu et al, , 2019Xu et al, , 2020Roberts et al, 2017).…”
Section: Bio-elementsmentioning
confidence: 99%
“…By comparing this grouping to previously published chemical analyses of penguin droppings, the authors confirmed that the group of bio-elements is representative of the species of interest, and so could be used to understand changes in penguin numbers back in time. R-cluster analysis, which has been used worldwide, is often considered the most effective tool to identify ornithogenic elements if a nearby reference site (i.e., a nearby lake without avian inputs) is not available to distinguish the natural, background element concentrations (Zale, 1994;Sun et al, 2000Sun et al, , 2004Liu et al, 2005Liu et al, , 2006cHuang et al, 2009aHuang et al, , 2011Xu et al, 2011Xu et al, , 2016Xu et al, , 2019Xu et al, , 2020Roberts et al, 2017).…”
Section: Bio-elementsmentioning
confidence: 99%
“…Primary productivity/surface productivity (Berg, Melles, et al, 2019 ; Emslie, 2021 ; Xu et al, 2020 )…”
Section: Live Mosses and Peatsmentioning
confidence: 99%
“…Analyses of dietary and/or stable isotope composition of animal remains reflects the environment in which the animals were feeding (e.g., in polynyas versus loose pack ice), which sheds light on sea ice conditions, and more broadly, can inform us of species responses to environmental change (Berg, White, Hermichen, et al, 2019 ; McClymont et al, 2022 ) (Tables 1 and 2 ). Several studies indicate that episodic occupation of sites by Adélie penguins on the Antarctic continent (e.g., Xu et al, 2020 ) reflects periods of enhanced marine productivity and greater nesting site availability during past warmer climates, in particular the penguin ‘optimum’ (~2–5 million years ago, Ma) (see Younger et al ( 2016 ) and references within). Seal hairs (Hodgson & Johnston, 1997 ) and changes in the deposition of bio‐elements from penguin guano (Sun et al, 2000 ) can be used as proxies for population size; the latter study finding a peak in population size corresponding to a time of high precipitation (~1.4–1.8 ka), suggesting a climatic influence.…”
Section: Animal Coloniesmentioning
confidence: 99%
See 1 more Smart Citation